Myocardial dysfunction occurs prior to changes in ventricular geometry in mice with chronic kidney disease (CKD). Issue 5 (20th March 2016) - Winterberg, Pamela D.; Jiang, Rong; Maxwell, Josh T.; Wang, Bo; Wagner, Mary B.
Abstract: Uremic cardiomyopathy is responsible for high morbidity and mortality rates among patients with chronic kidney disease (CKD), but the underlying mechanisms contributing to this complex phenotype are incompletely understood. Myocardial deformation analyses (ventricular strain) of patients with mild CKD have recently been reported to predict adverse clinical outcome. We aimed to determine if early myocardial dysfunction in a mouse model of CKD could be detected using ventricular strain analyses. CKD was induced in 5‐week‐old male 129X1/SvJ mice through partial nephrectomy (5/6Nx) with age‐matched mice undergoing bilateral sham surgeries serving as controls. Serial transthoracic echocardiography was performed over 16 weeks following induction of CKD. Invasive hemodynamic measurements were performed at 8 weeks. Gene expression and histology was performed on hearts at 8 and 16 weeks. CKD mice developed decreased longitudinal strain (−25 ± 4.2% vs. −29 ± 2.3%; P = 0.01) and diastolic dysfunction (E/A ratio 1.2 ± 0.15 vs. 1.9 ± 0.18; P < 0.001) compared to controls as early as 2 weeks following 5/6Nx. In contrast, ventricular hypertrophy was not apparent until 4 weeks. Hearts from CKD mice developed progressive fibrosis at 8 and 16 weeks with gene signatures suggestive of evolving heart failure with elevated expression of natriuretic peptides. Uremic cardiomyopathy in this model is characterized by early myocardial dysfunction which preceded observable changes in ventricular geometry. The model ultimately resulted in myocardial fibrosis and increased expression of natriuretic peptides suggestive of progressive heart failure. Abstract : Mice undergoing the partial nephrectomy model of chronic kidney disease (CKD) develop alterations in diastolic function and myocardial deformation prior to ventricular hypertrophy. Uremic cardiomyopathy in this model is characterized by diastolic dysfunction with preserved ejection fraction, ventricular hypertrophy, and progressive myocardial fibrosis. Calcium handling does not appear to contribute to impaired myocardial relaxation in mice with CKD.